Effect of Magnetic Field on Plasma Zn, Cu and Malondialdehyde Levels and Na+-K+ Atpase Activity of Isolated Diaphragmatic Muscle in a Diabetic Rat Model - DEMIRKAZIK*, A.; YUCEBILGIC†, G.; EMRE‡, M.; PELIT‡, A.; CETIN§, A.; GULTURK¶, S.; KAVAK#, S. (Asian Journal of Chemistry, 2009)
The aim of this study is to investigate the effect of magnetic field(MF) on plasma Zn, Cu and malondialdehyde (MDA) levels and Na+-K+ATPase activity of isolated diaphragmatic muscle in a diabetic rat model.Rats allocated as control (n = 10), diabetes mellitus (DM) (n = 10), MFexposed(MFE) (n = 10) and DM plus MF-exposed (DM-MFE) (n = 10)groups. After induced DM, the MF were exposed to MF in solenoid165 minutes every day during 1 month. Cardiac blood was obtainedand the plasma Zn, Cu and MDA levels and Na+- K+ ATPase activity ofdiaphragmatic muscle were determined. Plasma Cu level of the controlwas significantly lower than those of the DM and MFE (p < 0.05).Plasma Zn level of the DM-MFE was significantly lower than those ofthe control, DM and MFE (p < 0.05). Plasma MDA level of the DMwas significantly higher than those of the control, MFE and DM-MFE(p < 0.05). Diabetes mellitus and magnetic field increase plasma Cu leveland do not affect plasma Zn level, but MF plus DM decreases its level.While DM increases plasma MDA level, MF has opposing effect onMDA level. Diabetes mellitus decreases Na-K ATPase of rat diaphragmaticmuscle and MF elevates its level to normal.